The Influence of Leadership, Workload and Work Environment on Nurse Performance Through Organizational, Citizenship Behavior at Muhammad Sani hospital - Siti Bakdiah; Bambang Satriawan; Sri Yanti (Studi Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study examines the effects of leadership, workload, and work environment on nurse performance through OCB as a mediating variable at Muhammad Sani Hospital. Methodology/approach: The study uses a quantitative approach with survey methods, collecting primary data through questionnaires distributed to 180 nurses. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 to assess both direct and mediating effects among variables. Results/Findings: Leadership, workload, and work environment do not directly affect nurse performance, but OCB has a significant positive impact and mediates the effects of workload and work environment on performance. Conclusions: Nurse performance improves mainly through strengthening OCB. Supportive environments and balanced workloads foster OCB, while leadership should focus on encouraging cooperative behaviors to enhance service quality. Limitations: The study was limited to one hospital, so results may not apply broadly. Future research should include more hospitals and additional factors like job satisfaction or commitment. Contribution: This study highlights OCB as a key mediator in performance improvement and offers practical insights for hospitals to enhance nurse performance through better leadership, workload balance, and supportive environments.